TINJAUAN YURIDIS PEREMPUAN SEBAGAI KORBAN KEKERASAN DALAM RUMAH TANGGA MENURUT UNDANG-UNDANG NOMOR 23 TAHUN 2004 TENTANG PENGHAPUSAN KEKERASAN DALAM RUMAH TANGGA - Muahammad Yusuf (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
ABSTRACT HAM stands for Human Rights, where each word has meaning. The word "rights" in this case means belonging or power over something, while "Asasi" is something that is primary and fundamental. So, the definition of human rights in a nutshell is a fundamental and basic thing possessed by humans. In practice, there are many human rights violations that occur around us that we usually know in terms of domestic violence (abbreviated as domestic violence). Domestic violence is an act carried out in the household by a husband, wife, and child which has a negative impact on physical, psychological, and harmonious relations in accordance with Article 1 of Law Number 23 of 2004 concerning the Elimination of Domestic Violence (PKDRT Law).The method used in this study is a normative juridical method, data or information obtained through library research. From the results of the literature research, secondary data were obtained which included primary legal materials, secondary legal materials, and tertiary legal materials. The problem that the writer discussed in this thesis is the factors that cause the occurrence of domestic violence and legal efforts that can be done by women as victims of domestic violence according to Law Number 23 of 2004 concerning the Elimination of Domestic Violence.Based on the results of the study it can be concluded that the factors causing domestic violence in the legal area of Samarinda city are poverty / economic factors, unstable psychological conditions of the perpetrators, and public perceptions that are wrong in looking at domestic violence issues. Of the several factors, the main factors that cause domestic violence are poverty / economic crush and women who are married in marriage get domestic violence treatment, husbands can be said to have committed domestic violence and can be threatened with crimes as Article 44 of the PKDRT Law and can say to have committed human rights violations. The wife who was treated violently by her husband complained about the existence of domestic violence to the police to be processed on the basis of having committed abuse or domestic violence. Keywords: domestic violence, crime, human rights